Sequencing DNA using mass spectrometry for ladder detection. - Taranenko, N I (1998)
Sequencing of DNA fragments of 130 and 200 bp using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry for DNA ladder detection was demonstrated. With further improvement in mass resolution and detection sensitivity, mass spectrometry shows great promise for routine DNA sequencing in the future.